The role of sex and gender role self-concept in stress reactivity: evidence from the Trier Social Stress Test (TSST) - Zintel, Stephanie; Schmidt, Laura; Neubauer, Andreas B.; Stoffel, Martin; Rafiee, Yasaman; Ditzen, Beate; Sieverding, Monika (Psychoneuroendocrinology, 2025)
Aim - To investigate biological sex and gender role self-concept in stress reactivity, utilizing the Trier Social Stress Test for Groups (TSST-G). - Method - A sample of 175 participants (56% women, M = 39.2 years, SD = 12.5) underwent the TSST-G. Subjective and biological stress indicators (salivary cortisol sCort) and sex hormones (estradiol, testosterone) were assessed. Gender role self-concept (Bem Sex Role Inventory), in particular agency (stereotypically associated with masculinity), and biological sex were considered. - Results - Women reported higher subjective stress, whereas men had a steeper increase in sCort levels throughout the TSST-G. Results suggest lower subjective stress responses in more agentic people, independently of sex. Agency was not associated with sCort levels. Exploratory analyses revealed no interaction between agency and sex hormones. - Conclusion - Our study identified correlations between gender role self-concept and subjective stress in a large, non-student sample. The data confirm associations of biological sex with sCort response.
Online verfügbar: 4. Mai 2025, Artikelversion: 13. Mai 2025
Gesehen am 21.08.2025